PENGEMBANGAN MEDIA GAYANGHETUM (GAMBAR WAYANG HEWAN DAN TUMBUHAN) DALAM PEMBELAJARAN TEMATIK TERINTEGRASI KELAS IV SD - Oktavianti, Rizki; Wiyanto, Agus (Universitas Pendidikan Indonesia, 2014)
Lack of concentration learned in grade IV Elementary School N 01 Tegorejo due to the learning process is still given over monotonous so easily bored students in learning activities, and the lack of use of the environment as a medium of learning were encountered in the learning process. An environment where learning can simultaneously be used as a study material which has many benefits. Management and efficient utilization of the environment can produce a product that teaching has a high educational level. Based on these problems GAYANGHETUM media can be used as an alternative to learning. This type of research is the Research and Development is the development of instructional media. Media GAYANGHETUM is the development of an effective puppet media for use in learning. Analysis of test media expert GAYANGHETUM feasibility level by 90%, feasibility of matter 88.33%, and 91.48% was obtained from a questionnaire students who agree GAYANGHETUM media used in the study.Keywords: media gayanghetum, integrated thematic learning, class IV semester 1 elementary school.